Correlation Between Renal Cortical Stiffness and Histological Determinants by Point Shear-Wave Elastography in Patients With Kidney Transplantation. (December 2017) - Chiocchini, A. L. Croci; Sportoletti, C.; Comai, G.; Brocchi, S.; Capelli, I.; Baraldi, O.; Bruno, P.; Conti, F.; Serra, C.; Meola, M.; Zompatori, M.; La Manna, G.
Introduction: Renal allograft biopsy is the gold standard for the detection of histological lesions of chronic allograft dysfunction. The identification of a noninvasive routine test would be desirable. Elastosonography is used to assess tissue stiffness according to viscosity, and no data are available on the use of point quantification shear-wave elastography (ElastPQ) for the evaluation of renal chronic lesions. Research Question: To evaluate the feasibility of ElastPQ to assess cortical allograft stiffness and to determine the correlation of clinical, biological, and pathological factors with the diagnostic accuracy of kidney stiffness values in patients with histological lesions. Design: Forty-two patients underwent kidney transplant biopsy and 10 valid measurements of ElastPQ, blindly performed by 2 operators. The interobserver reproducibility was assessed according to intraclass correlation coefficient. The ElastPQ measurements and the clinical data were compared using the Spearman correlation analysis. Results: 97.6% reliable measurements were obtained using ElastPQ, with an excellent interobserver agreement. The kidney stiffness was significantly higher in the patients with a time since transplantation >12 months and was correlated with chronic lesions (interstitial fibrosis, tubular atrophy transplant glomerulopathy, and mesangial matrix), with the interstitial fibrosis/tubular atrophy, score and with the sum of the scores of the chronic lesions. Mesangial matrix increase is the only independent determinant of kidney stiffness. Discussion: ElastPQ is a noninvasive, reproducible, and sensitive diagnostic tool able to detect moderate/severe chronic lesions. Its routine use during follow-up can identify patients eligible for biopsy, which remains the gold standard exam for detecting chronic allograft dysfunction.